Peningkatan Kualitas Pelayanan melalui Daya Tanggap dan Keandalan Staf untuk Kepuasan Pasien di RSKDGM Manado - Wandha Cindhy Mandalika; Jeanette I. Ch. Manoppo; Oksfriani Jufri Sumampouw (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve the quality of services at the Manado Regional Dental and Oral Hospital (RSKDGM) by strengthening two essential aspects of healthcare delivery: the responsiveness and reliability of medical staff. The background of this activity stems from persistent patient complaints regarding service quality, including delays, ineffective communication, and a lack of empathy from some medical personnel. These issues are particularly concerning given that RSKDGM is widely recognized for its complete and modern dental facilities. The methods used in this activity included intensive training sessions for both medical and non-medical staff on excellent service delivery, simulations of daily service situations to enhance staff readiness in handling various types of patients, and participatory evaluation sessions involving patients and hospital management. These evaluations aimed to gather direct feedback from patients on the changes implemented and to serve as input for continuous improvement. The results of the activity showed a significant increase in staff awareness of the importance of providing fast, accurate, and empathetic service. Staff members became more communicative, responsive to patient needs, and demonstrated higher levels of professionalism. From the patients’ perspective, there was an improvement in satisfaction, particularly regarding the speed of service and the quality of interactions with medical personnel. This community service project made a tangible contribution to fostering a patient-centered service culture and strengthening the relationship between healthcare providers and the community. Furthermore, the approach used in this program can serve as a model for continuous training in similar hospitals, especially those specializing in dental care.